An open secret. (Economist, 2005)
The article focuses on sharing intellectual property and on the non-proprietary, open-source community. On January 11th this year, IBM pledged 500 of its existing software patents to the open-source community, to be placed into a patent "commons" that allows open-source software developers to use the innovations and build upon them without risk of infringement. Since then, some other companies have taken similar initiatives. In May, Nokia said it would not assert its patents against the inner code of Linux, a popular open-source computer operating system. In June, Red Hat, a big Linux distributor, said that it, too, would contribute to a patent commons. In September, Computer Associates donated 14 patents for free use by the open-source community. Open Source Development Labs, an industry forum, has offered to act as a repository for patent-commons projects. The trend towards open software code is an example of a bigger development in the technology industry: a new approach towards collaboration and "open innovation" that at times seems to work around the traditional intellectual-property system, and at times is directly fostered by it. IBM profits from open-source (and particularly Linux) in two ways. First, open-source software is by some measures less expensive than proprietary software, so using it lowers the overall cost a customer pays for IBM's computers, applications or services. Second, it provides a common platform on top of which IBM can build and sell special applications and services. A small army of activists with names such as Electronic Frontier Foundation, Creative Commons, IP Watch, Public Patent Foundation, Centre for the Public Domain, the Open Knowledge Foundation and the Foundation for a Free Information Infrastructure, which was instrumental in blocking a European Union directive to harmonise software-patent policy this summer, are opposed to the current system of intellectual property.